Clostridium difficile on YouTube: A need for greater focus on prevention. Issue 2 (March 2018) - Basch, Corey H.; Hillyer, Grace C.; Garcia, Philip; Basch, Charles E.
Abstract: The purpose of this study was to describe the content of the most popular YouTube videos related to Clostridium difficile . Across all sources, the kinds of content most likely to be included in the videos was general information, overuse of antibiotics, and symptomatic diarrhea. Health professionals can contribute to existing social media messages related to C. difficile with comprehensive messages that include means for prevention.